Assessing Seismic Response in Dual Tower Connected Structures at Different Storey Levels Through Fixed and Flexible Connections (Journal of Science and Engineering, 2026)
Skybridges are horizontal connectors between towers, influencing structural dynamics by enhancing coupling and altering dynamic load responses. This study examines seismic performance of dual eight storey tower buildings interconnected by 8 m x  14 m skybridges at three levels (first and second, third and fourth, and seventh and eighth floors). The passive isolations systems using Lead Rubber Bearings (LRB) and High Damping Rubber Bearings (HDRB) are compared with conventional rigid connections. Nonlinear time history analyses are conducted in ETABs v20.1 using matched spectral records of the New Zealand-2021 and Loma Prieta-1989 earthquakes, based on Nepal’s building code NBC 105:2020 design response spectrum (475-year return period), and unscaled Gorkha-2015 earthquake. Parameters such as base shear, isolator displacement, structure displacement, drift, and hysteresis energy are analyzed. Results show a 46% base shear reduction with isolated skybridges. Lower floor isolation effectively minimizes top story displacements and inter storey drifts due to improved decoupling. Upper floor isolation leads to larger isolator displacements. LRB exhibit 14% higher energy dissipation than HDRBs. Maximum utilization of HDRB occurs under high displacements within the permissible design limits. For the cyclic load and rapid force reversal, HDRB shows stable force-displacement behavior and reduced cumulative damage.